2009
DOI: 10.1177/0748233709348386
|View full text |Cite
|
Sign up to set email alerts
|

The biocontaminants and complexity of damp indoor spaces: more than what meets the eyes

Abstract: Nine types of biocontaminants in damp indoor environments from microbial growth are discussed: (1) indicator molds; (2) Gram negative and positive bacteria; (3) microbial particulates; (4) mycotoxins; (5) volatile organic compounds, both microbial (MVOCs) and non-microbial (VOCs); (6) proteins; (7) galactomannans; (8) 1-3-beta-D-glucans (glucans) and (9) lipopolysaccharides (LPS--endotoxins). When mold species exceed those outdoors contamination is deduced. Gram negative bacterial endotoxins, LPS in indoor env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 324 publications
(449 reference statements)
2
58
0
Order By: Relevance
“…27,28 With recent understandings of the innate immune system components the serendipitous interaction of many types of biocontaminants in damp indoor environments, including molds, is becoming more fully understood. 29,30 In this context, the relationship among damp environments, poor housing, and asthma is becoming appreciated. 31 Studies combining weatherization and healthy home interventions with asthma education are beginning to significantly improve childhood asthma control 32 and lower health-care costs.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 With recent understandings of the innate immune system components the serendipitous interaction of many types of biocontaminants in damp indoor environments, including molds, is becoming more fully understood. 29,30 In this context, the relationship among damp environments, poor housing, and asthma is becoming appreciated. 31 Studies combining weatherization and healthy home interventions with asthma education are beginning to significantly improve childhood asthma control 32 and lower health-care costs.…”
Section: Discussionmentioning
confidence: 99%
“…Carcinogenic, mutagenic, teratogenic, heptotoxic, nephrotoxic, immunodeppressants and inhibition of protein synthesis (Thrasher and Crawley, 2009). …”
Section: Application Of Bio-sensorsmentioning
confidence: 99%
“…Of the mold particulates the greatest concern is the nano-particulates at or less than 0.3 microns shed from mold colonies. Field studies of water-damaged homes have shown concentrations of nano-particulates in indoor dust that are at least 1000 times or greater than the indoor air mold spore counts [12][13][14][15][16][17][18]. These particulates contain 1, 3-beta glucans, a variety of fungal proteins that include substrate enzymes as well as mycotoxins.…”
Section: Particulatesmentioning
confidence: 99%
“…All of these situations lead to both hidden as well visual signs of fungal and bacterial growth. For simplicity, "water intrusion" will be used as all encompassing term [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%